Method and Device for Reducing the Toxicity of Diesel Engine Exhaust Gases - N.V, Byshov; A.N, Bachurin; I.Yu, Bogdanchikov; D.O, Oleynik; Yu.V., Yakunin; A.V, Nelidkin (International Journal of Engineering and Technology, 2018)
The aim of the article is to develop a method and a device for reducing the toxicity of exhaust gases of diesel engines and reducing noise taking into account the current mode of operation of the engine. This is done with the help of installing a liquid catalyst (LC) into the exhaust system, ensuring the processes of trapping, chemical bonding and neutralization of toxic components and soot particles in the aerosol chamber while the vortex flow is being processed by a neutralizing solution supplied under pressure. Then the flow is divided into phases and toxic components and soot are separated in the centrifugal swirl drop separator (SDS).The developed and tested design of an exhaust gas cleaning device installed instead of the standard D-120 engine exhaust system and an automated cleaning process control system make it possible to reduce the toxicity of exhaust gases (EG): nitrogen oxides by 40 %, hydrocarbons by 43 % and soot by 70 %. The noise level of its work in enclosed spaces was reduced by 16â€“22 %. The device also had low gas-dynamic resistance.The investigation methodology is based on the use of modern methods and measuring devices. Exhaust gas tester META â€œAutotest CO â€“ CH â€“ CO2 â€“ O2 â€“ Î» â€“ NOxâ€ was used to measure the toxicity of exhaust gases. To measure smoking at the exhaust of the diesel engine, the opacity meter META-01MP was used. The gas flow velocity was measured with ATT-1004 thermo-anemometer, the noise level of the tractor was recorded with noise and vibration meter VSHVâ€“003â€“M2, and the fuel consumption with SIRT-1 meter.Theoretical studies were carried out on the basis of the laws of gas dynamics, the modern theory of statistical analysis, and experiment planning techniques. When developing an experimental LC model, dependencies were obtained, which allow to achieve the optimal design and technological parameters of the wet cleaning system for diesel exhaust gases.The optimization of the design parameters and the processing of experimental data were carried out with the help of modern software using the methods of mathematical statistics using computers.The current methods of reducing the toxicity of engines consist primarily in improving the design of engines, in order to influence the nature of the working process, the use of alternative fuels and additives, exhaust gas recirculation, as well as installing various types of exhaust gas catalytic systems. Measures related to the introduction of constructive changes in engines require some major restructuring of the industry, which is difficult to achieve in modern conditions. Alternative fuels have not yet been widely used in agriculture. Therefore, today the most effective and acceptable means of achieving environmental standards is the installation of various mobile catalysts in the exhaust system, as well as devices for trapping soot particles. The use of this exhaust gas cleaning system for diesel engines functioning in enclosed spaces can significantly improve the working conditions of the personnel and have a slight effect on the power and fuel-economic performance of the power unit, reducing the power of the D-120 engine of the T-30 tractor equipped with an upgraded exhaust system when taking external speed characteristics averaged 1.6 %, the torque was 1.5 % and the increase in specific fuel consumption was 1.8 %.In this paper we used materials from scientific publications indexed by bibliographic abstract databases of Scopus and Web of Science.Â Â Â